2022
DOI: 10.3390/cells11152363
|View full text |Cite
|
Sign up to set email alerts
|

ENO2 Promotes Colorectal Cancer Metastasis by Interacting with the LncRNA CYTOR and Activating YAP1-Induced EMT

Abstract: The glycolytic enzyme enolase 2 (ENO2) is dysregulated in many types of cancer. However, the roles and detailed molecular mechanism of ENO2 in colorectal cancer (CRC) metastasis remain unclear. Here, we performed a comprehensive analysis of ENO2 expression in 184 local CRC samples and samples from the TCGA and GEO databases and found that ENO2 upregulation in CRC samples was negatively associated with prognosis. By knocking down and overexpressing ENO2, we found that ENO2 promoted CRC cell migration and invasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…We hypothesized that the ENO2-mediated glycolysis process might play a crucial role in supplying energy for anoikis resistance in ATC cells. Previous studies have shown that ENO2 is significantly involved in the development of various tumors ( 22 , 28 , 53 ), prompting our assumption that regulating ENO2 expression might influence the fate of cells under detached culture conditions. Our in vitro experiments demonstrated that the knockdown of ENO2 significantly increased cell apoptosis in the SW1736 and 8305C cells, coupled with a significant decrease in sphere formation.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…We hypothesized that the ENO2-mediated glycolysis process might play a crucial role in supplying energy for anoikis resistance in ATC cells. Previous studies have shown that ENO2 is significantly involved in the development of various tumors ( 22 , 28 , 53 ), prompting our assumption that regulating ENO2 expression might influence the fate of cells under detached culture conditions. Our in vitro experiments demonstrated that the knockdown of ENO2 significantly increased cell apoptosis in the SW1736 and 8305C cells, coupled with a significant decrease in sphere formation.…”
Section: Discussionmentioning
confidence: 93%
“…It serves as a general marker in cell differentiation in neuroendocrine tumors and has been noted to be a well-established tumor biomarker in various types of cancers, including prostate cancer, small-cell lung cancer, and the microvascular invasion status of liver cancer ( 23 - 25 ). Several studies have suggested that ENO2 contributes to metastasis by stimulating glycolytic activity ( 26 - 28 ). The forced expression of oncogenes rescues the anoikis of mammary epithelial cells by increasing glucose utilization and decreasing oxidative stress levels ( 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the EMT pathway, which played a pivotal role in CRC progression, was upregulated in C2, suggesting that this subtype may be highly malignant (Fig. 2 C) [ 20 , 21 ]. To identify subtypes in novel datasets, a gene classifier based on centroid was developed with reference to an article [ 16 ].We constructed a PAM classifier based on the differential genes of cell lines and apply it to the typing of TCGA cohort.…”
Section: Resultsmentioning
confidence: 99%
“…SNHG4 sponges miR‐204‐5p and promotes RCC cell proliferation and invasion 49 . The lncRNA CYTOR performs a remarkable function in promoting the development of digestive system tumors 50–52 . LINC00977 acts as an oncogene by binding STAT3 in ccRCC 53 .…”
Section: Discussionmentioning
confidence: 99%